2022
DOI: 10.3390/jcdd9080239
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Acute Coronary Syndromes: A Global Perspective

Abstract: Despite increasing evidence and improvements in the care of acute coronary syndromes (ACS), sex disparities in presentation, comorbidities, access to care and invasive therapies remain, even in the most developed countries. Much of the currently available data are derived from more developed regions of the world, particularly Europe and the Americas. In contrast, in more resource-constrained settings, especially in Sub-Saharan Africa and some parts of Asia, more data are needed to identify the prevalence of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
1
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 160 publications
3
35
1
5
Order By: Relevance
“…The leading cause of death in women in all industrialized countries is myocardial infarction although heart failure has different characteristics in women and its impact effects are greater in old age women than men. Also, stroke affects women more than men and the ischemic form is more frequent and affects more women than men [16,17]. The prevalent risk factors for stroke in women are several: increased platelet reactivity, higher level of coagulation factors, and sex-associated unique cardiovascular risk factors, such as pregnancy-related (i.e., pre-eclampsia and gestational diabetes), gynecological disorders (i.e., polycystic ovary syndrome, early menopause) and autoimmune or systemic inflammatory diseases [18].…”
Section: Discussionmentioning
confidence: 99%
“…The leading cause of death in women in all industrialized countries is myocardial infarction although heart failure has different characteristics in women and its impact effects are greater in old age women than men. Also, stroke affects women more than men and the ischemic form is more frequent and affects more women than men [16,17]. The prevalent risk factors for stroke in women are several: increased platelet reactivity, higher level of coagulation factors, and sex-associated unique cardiovascular risk factors, such as pregnancy-related (i.e., pre-eclampsia and gestational diabetes), gynecological disorders (i.e., polycystic ovary syndrome, early menopause) and autoimmune or systemic inflammatory diseases [18].…”
Section: Discussionmentioning
confidence: 99%
“…and Saudi Acute Myocardial Infarction Registry Program (STARS-1 Program) [25]. SPACE provides a comprehensive overview of current diagnostic and treatment strategies for acute coronary syndrome (ACS) patients in SA [24] [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Appropriate public health messaging to ensure timely presentation at hospitals 2 and education and bias mitigation training of healthcare personnel are of paramount importance, as is appropriate attention to recognizing accompanying symptoms of chest pain. 1 Protocol-driven, systems-based approaches to STEMI care have demonstrated reduced sex disparities in STEMI care and improved outcomes in women 2 and should be incorporated into practice. Female participant representation in clinical trials must be enhanced.…”
Section: Referencesmentioning
confidence: 99%
“…Despite improvements in acute coronary syndromes (ACS) care, globally, sex disparities remain. 1 Women with ST-segment elevation myocardial infarction (STEMI) present later, receive suboptimal care, and have worse outcomes than men. [1][2][3] In a single-center retrospective analysis of 809 STEMI patients undergoing primary PCI in Braga, Portugal, Oliveira et al reported sex disparities in presentation, management, and outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation